Analisis Isi Skripsi Kehumasan di Perguruan Tinggi - Rachmat Kriyantono (Universitas Muhammadiyah Ponorogo, 2020)
This study aims to prove three hypotheses, namely public relations theories have been widely adopted in the theses of public relations students, the theory that dominates public relations studies is the Theory of Excellence, and the most widely used of the method is qualitative. The researcher conducted a content analysis on student thesis in universities in Surabaya and Malang City in 2015 until 2019. The samples of this study were 388 theses of the students majoring in the Public Relations study. This study has proven the three hypotheses, namely the theses have applied Public Relations theories, the most widely used of the theory is Excellence theory, and the Qualitative method is the most widely used of the method. This research has also confirmed that the public relations field is not only focused on practice, but also theoretical studies. This study also confirms that the development of public relations in Indonesia is in line with the development of public relations in the United States, that is, from the practical dimension to the dimension of theoretical study.